Clergy's Viewpoint Change Toward Mental Health and Stigma on Mental Illness: A Short Course Training - Taghva, Arsia; Noorbala, Ahmad Ali; Khademi, Mojgan; Shahriari, Alireza; Nasr Esfahani, Mahdi; Asadi, Ali; Mohsenifar, Jafar; Yousefifard, Ali; Abolhassani, Moussa; Bolhari, Jafar; Hajebi, Ahmad; Rahnejat, Amir Mohsen; et al. (Frontiers in Psychiatry, 2022)
Background: Stigma is one of the main barriers in promoting the mental health. So the present study was designed with the purpose of reviewing clergy's viewpoint and regarding the effect of mental health workshops on them. Methods: For this study, By order of Iran's Health Ministry, a questionnaire was designed to examine the clergy’s viewpoints related to mental illnesses and the consequent stigma. 10 faculty members and psychiatrists confirmed the questionnaire’s validity after some modifications. In this research, 30 members of clergy from the main religious city in Iran “Qom” Seminary attended the training workshops for two days. The data obtained from the clergy's responses were analyzed using the SPSS software (ver.16) and descriptive and analytical tests. Also, the significance level was considered p<0.05 in all tests. The results exhibited that the mean and standard deviation (Mean ±SD) of the clergy’s attitude domain and awareness before the workshop was 1.90±26.30 and 1.64±8.31, respectively. Also, average and standard deviation (Mean ±SD) of their attitude domain and awareness after the workshop was 1.95±29.73 and 1.18±10.70, respectively. Discussion :The present study, which was designed to examine the clergy’s viewpoint towards the mental illnesses and the consequent stigma in the most considerable religious base in the country, illustrated that one strategy for reducing mental illness stigma in religious communities can be holding training sessions provided for promoting of the clergy’s awareness and attitude of mental health. Conclusion: There was a significant statistical difference between their awareness and attitude scores before and after the workshop (p<0.01). In the present research, the awareness and attitude of clergy towards mental health and stigma due to mental illness was relatively good and significantly increased by holding the workshop.